Partnership, empowerment and local development - Vasconcellos, Mário (2016)
This paper tries to understand how partnership between local organisations (associations, cooperatives,worker’s unions and others) and Government affects local development. It explores to what extent partnership is aneffective strategy for local development in areas of historical conflict between local Government and the localorganisations that defend the interests of family-based, small-scale rural producers. Particularly, this paper concentrateson debate of partnership as a mechanism of power sharing and empowerment of the people that historically have beenexcluded from the development process. Empirically, the paper is based on data collected in the municípios of Ourémand Igarapé-Miri, Northeast of Para State, Amazonia, Brazil.